Life Cycle Thinking in Small and Medium Sized Enterprises A case study of SMEs in the renewable energy industry - Eriksson, Emil; Nyberg, Joanna (My University, 2024)
This thesis explored the adoption and learning process of Life Cycle Thinking (LCT) among small and medium-sized enterprises (SMEs) in the renewable energy sector. As environmental sustainability has become more imperative, SMEs, representing a significant portion of businesses and carbon emissions in the EU, faced unique chal- lenges in implementing sustainable practices due to limited resources. This study, conducted in collaboration with the Swedish Life Cycle Centre, aimed to identify key challenges and needs in the greening process of SMEs. Through two qualitat- ive methods, a literature review and a case study based on interviews, the research investigated how SMEs adopted LCT, the components involved in their learning process, and strategies to advance their learning. Findings indicated that while SMEs exhibited a range of greening activities, these varied significantly based on company size and resources. Key steps in the learning process included recognising internal ambition, targeting easily achievable improvements, and fostering collab- oration within the supply chain. The study highlighted the necessity of adopting standards and frameworks to streamline LCT adoption. The research underscored the importance of tailored support from stakeholders and a supportive organisational culture in fostering sustainable practices. SMEs could advance their learning by em- bracing a triple loop learning mindset, incorporating strategic work, and leveraging stakeholder support eectively.
Keywords: SME; LCT; renewable energy industry; organisational learning; greening process; stakeholder support; environmental sustainability; EU green deal